198k views
3 votes
Simply 7 radical 3 minus 4 radical 6 plus sqrt of 48 minus sqrt 54

Simply 7 radical 3 minus 4 radical 6 plus sqrt of 48 minus sqrt 54-example-1
User Jottr
by
5.1k points

2 Answers

3 votes


image

User Gabriel Isenberg
by
4.7k points
6 votes

To simplify the above expression, let's simplify each radicals at first.

√3 and √6 cannot be further simplify.

Now √48 = √(16* 3)

=√16 * √3

= 4√3

Similarly, √54 = √(9*6)

=√9 *√6

=3√6

So, now we can write the above expression as:

7√3 - 4√6 + √48 - √54

= 7√3 - 4√6 + 4√3 - 3√6

= 11√3 - 7√6

User Pavelety
by
6.2k points